Analisis dan Pengujian Aplikasi Web Donasi Online dengan Pendekatan Metode Waterfall - Aryo Chandra; Muhammad Fauzan (PT Jurnal Cendekia Indonesia, 2025)
Digitalization in various industries has been driven by advances in information technology, including in the social sector through online donation platforms. The purpose of this study is to analyze and test an online donation web application developed using the Waterfall method. This method was chosen because of its systematic development structure, starting from the needs analysis stage, system design, implementation, and testing. The test results were carried out to ensure that the system's functionality runs according to the stated objectives, especially in terms of the login process, registration, donation management, and transaction reports. The test results showed that the application can operate well and meet user needs according to the designed scenario. Efficiency and usability analysis also showed good results. This study supports the development of social applications that can increase the ease and trust of people in donating online.